Clinical predictors of recurrent stenosis and need for re-intervention in the cephalic arch in patients with brachiocephalic AV fistulas. Issue 4 (July 2017) - Balamuthusamy, Saravanan; Reddi, Alagarsamy Lakku; Madhrira, Machaiah H.; Sankarapandian, Balamurugan; Nguyen, Peter; Vallurupalli, Avinash; Gabbard, William; Jalandhara, Nishant; Yurvati, Albert
Introduction: Cephalic arch stenosis is one of the most common reasons for repeated endovascular intervention and eventual abandonment of access in hemodialysis patients. There is no prediction model to identify risk factors for recurrent cephalic arch stenosis. We have developed a mathematical model to predict the need for reintervention in brachiocephalic (BC) fistulas with recurrent cephalic arch stenosis. Methods: Single-center retrospective analysis of 143 patients with a BC fistula referred to the vascular clinic for access dysfunction who underwent cephalic arch angioplasty were included for the analysis. Twelve-month post-index angioplasty data were analyzed using parametric, non-parametric and multiple regression models using SPSS software. Results: The mean need for re-intervention in 1 year since first index visit was 2.46 ± 1.404. Statistically significant correlation (p≤0.001) for re-intervention was observed with the severity of stenosis at index visit, access flow, vessel wall diameter proximal to the stenosis, average venous pressure >50% of the delivered blood flow rate and prolonged bleeding for >30 minutes as a reason for referral. Three equations have been derived for calculating the need for re-intervention based on the diameter of the vessel wall proximal to the stenosis. Conclusions: Risk stratification of BC fistulas utilizing the above parameters could enable clinicians to identify accesses that are at risk for multiple re-interventions. Early identification of accesses that are at high risk for re-interventions at the cephalic arch might prolong access survival and reduce the cost for intervention by utilizing alternate strategies.